Fiscal decentralization: a survey on its impact on economic growth and its challenges - Yusof, Yusniliyana; Shahari, Farihana; Asuhaimi, Fadhilah Abdullah (International Journal of Research and Innovation in Social Science (IJRISS), 2025)
Advocates of decentralization contend that it is a fundamental catalyst for economic progress, as it bolsters the operational capacities of local governments, hence augmenting efficiency and fostering competition. However, proponents of an opposing perspective contend that decentralization could potentially hinder economic progress through the inequitable allocation of resources, macroeconomic instability, and instances of corruption. The persistence of dispute has endured across several decades of rigorous theoretical and empirical examination. The majority of empirical research conducted in this field has focused on analyzing the impact of decentralization on economic growth in both developed and developing nations. Although there is a lack of consistent findings, a limited number of studies have focused on the obstacles and difficulties that may impede the effectiveness of decentralization in fostering economic growth and development. The comprehension of the role and challenges associated with decentralization is a vital consideration for policymakers, as it is recognized as a significant institutional element. Therefore, this study aims to conduct one of the initial surveys to synthesize the existing theoretical and empirical literature on decentralization. This study provides a concise review of the theoretical discourse around fiscal decentralization, examining both the arguments in favor of and against it to comprehend its potential effects on economic growth. This study presents empirical data on the relationship between fiscal decentralization and economic growth, where mixed findings were reported. Furthermore, we emphasize the persistent obstacles that hinder the progress of fiscal decentralization, namely in terms of fiscal autonomy, limited resources, political discord, and oversight by the central government. In conclusion, our research article provides a comprehensive analysis and offers a set of policy recommendations aimed at facilitating the attainment of effective decentralization.